Autismo: le difficoltà genitoriali e l’intervento gestaltico integrato - Lorena Vincenza Perrone, Claudia Tornetta (Phenomena Journal)
The following article aims to illustrate the initial stages of a research that intends to confirm the hypothesis that parental support, in the case of families in which a person with an autism spectrum disorder is inserted, it is fundamental and requires treatment. integrated to ensure the success of the various interventions, including cognitive and behavioral, proposed to these subjects and presented as electives. A questionnaire was constructed to survey the parental difficulties in adapting and adhering to the cognitive behavioral treatments of their children with autism spectrum disorder. In this first phase, an investigation was launched by administering it to the parents of children with autism who follow a cognitive behavioral treatment, which requires a modification of the home environment and daily routine to adhere to the intervention plan, with the aim of deepening and detect any difficulties these parents face in following the therapists' directions. The analysis of the data collected would allow us to confirm the presence of difficulties in the management and implementation of the strategies proposed by the cognitive-behavioral treatments and that this could negatively influence the outcome of the treatment. The proposal of an integrated Gestalt intervention provides for constant parental support from the psychotherapist and an openness and greater flexibility of the treatments tailored to the patient, taking into account the parental difficulties in supporting the child's therapy, becoming an integral part of it, fundamental for the good result. Parents suffer and experience frustration at their inability to manage their children. Their suffering becomes, in a Gestalt frame, a sufference of the field and therefore also of the subject with autism who is inserted into it, who experiences it from a neurological point of view due to the pressures that the rigidity of the intervention requires and from a point of view of climate, environment and family system.